Regime transformations and global realignments : Indo-European dialogues on the post-cold war world - Ahuja, Kanta; Coppens, Huub.; Wusten, Herman van der. (New Delhi : Sage, 1993)
Papers presented at a seminar organized by Indo-Dutch Programme on Alternatives in Development in Netherlands, December 7-10, 1992.
Includes bibliographical references.
Keywords: Cold War; International relations